2020
DOI: 10.1186/s12872-020-01591-1
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of ambrisentan in Chinese patients with connective tissue disease-pulmonary arterial hypertension: a post-hoc analysis

Abstract: Background: The efficacy and safety of ambrisentan has been previously evaluated in Chinese patients with pulmonary arterial hypertension (PAH). This post-hoc analysis assessed the efficacy and safety of ambrisentan in a subgroup of connective tissue disease (CTD) patients with PAH. Methods: In this open-label, single-arm study, patients received ambrisentan 5 mg once daily for 12 weeks, followed by 12-week dose titration period (dose up to 10 mg). Efficacy endpoints included change from baseline in exercise c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
1
0
0
Order By: Relevance
“…The present study revealed that the overall incidence of CV events in patients with CHD was 3.4%, with the incidence of serious adverse events being only 0.019%. This is consistent with the findings of previous studies performed on CV disease ( 9 ). For instance, the HF-ACTION trial evaluated the safety of CPET in 2,037 patients with heart failure (with a median left ventricular ejection fraction of 25%), in which only 2 cases of ventricular arrhythmias were observed while no fatal events occurred ( 10 ).…”
Section: Discussionsupporting
confidence: 94%
“…The present study revealed that the overall incidence of CV events in patients with CHD was 3.4%, with the incidence of serious adverse events being only 0.019%. This is consistent with the findings of previous studies performed on CV disease ( 9 ). For instance, the HF-ACTION trial evaluated the safety of CPET in 2,037 patients with heart failure (with a median left ventricular ejection fraction of 25%), in which only 2 cases of ventricular arrhythmias were observed while no fatal events occurred ( 10 ).…”
Section: Discussionsupporting
confidence: 94%